2006
DOI: 10.1016/j.jbankfin.2005.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Bank loan supply and monetary policy transmission in Germany: An assessment based on matching impulse responses

Abstract: This paper addresses the credit channel in Germany by using aggregate data. We present a stylized model of the banking firm in which banks decide on their loan supply in the light of expectations about the future course of monetary policy. Applying a VAR model, we estimate the response of bank loans to a monetary policy shock taking account of the reaction of the output level and the loan rate. We estimate our model to evaluate the response of bank loans by matching the theoretical impulse responses with the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
24

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 28 publications
0
30
0
24
Order By: Relevance
“…Hülsewig et al (2006) examined the bank lending channel in Ger many, using ag gregate data and the VAR model. They found that a contraction in monetary policy decreases bank loans.…”
Section: Evidence Of the Bank Lending Channel: Macro-level Studymentioning
confidence: 99%
“…Hülsewig et al (2006) examined the bank lending channel in Ger many, using ag gregate data and the VAR model. They found that a contraction in monetary policy decreases bank loans.…”
Section: Evidence Of the Bank Lending Channel: Macro-level Studymentioning
confidence: 99%
“…However, for the representative bank B t corresponds to the amount of central bank credit that is needed to fulfill the minimum reserve requirement (Hűlsewig et al, 2006).…”
Section: Banksmentioning
confidence: 99%
“…Finally, to estimate the elasticity of the loan supply with respect to the loan rate we rely on Huelsewig, Mayer and Wollmershaeuser (2005) who use aggregate data to estimate the response of bank loans to a monetary policy shock. As a robustness check, we also use the estimates in King (1986), and we notice that the sensitivity of the change in the loan rate to this elasticity parameter is extremely low.…”
Section: An Estimate Of the Capital Outflows Due To The Reformmentioning
confidence: 99%
“…a Guiso (2003) b Lower and upper bounds from Capitalia (2003) c Huelsewig, Mayer and Wollmershaeuser (2005); King (1986) Note: by rearranging equation (8) we obtain…”
Section: Sourcesmentioning
confidence: 99%